Priming healthy eating. You can't prime all the people all of the time. (1st June 2015) - Forwood, Suzanna E.; Ahern, Amy L.; Hollands, Gareth J.; Ng, Yin-Lam; Marteau, Theresa M.
Highlights: Mock adverts were used to prime healthy eating in two studies. The primes increased fruit preference in more educated and hungry individuals. Priming did not alter fruit preference in less educated or non-hungry individuals. The mechanism of prime action may be dependent on participant characteristics. Primes effective in some participants cannot be assumed to be effective in others. Abstract: Objective: In the context of a food purchasing environment filled with advertising and promotions, and an increased desire from policy makers to guide individuals toward choosing healthier foods, this study tests whether priming methods that use healthy food adverts to increase preference for healthier food generalize to a representative population. Methods In two studies (Study 1 n = 143; Study 2 n = 764), participants were randomly allocated to a prime condition, where they viewed fruit and vegetable advertisements, or a control condition, with no advertisements. A subsequent forced choice task assessed preference between fruits and other sweet snacks. Additional measures included current hunger and thirst, dietary restraint, age, gender, education and self-reported weight and height. Results In Study 1, hunger reduced preferences for fruits (OR (95% CI) = 0.38 (0.26–0.56), p  <   0.0001), an effect countered by the prime (OR (95% CI) = 2.29 (1.33–3.96), p  = 0.003). In Study 2, the effect of the prime did not generalize to a representative population. More educated participants, as used in Study 1, chose more fruit when hungry and primed (OR (95% CI) = 1.42 (1.13–1.79), p  = 0.003), while less educated participants' fruit choice was unaffected by hunger or the prime. Conclusion This study provides preliminary evidence that the effects of adverts on healthy eating choices depend on key individual traits (education level) and states (hunger), do not generalize to a broader population and have the potential to increase health inequalities arising from food choice.